An efficient biocatalytic system for floxuridine biosynthesis based on Lactobacillus animalis ATCC 35046 immobilized in Sr-alginate - Cappa, Valeria Alejandra (2014)
An efficient and green immobilized biocatalyst is herein reported to obtain 5-fluorouracil-2′-deoxyriboside (5FUradRib), an antimetabolite known as Floxuridine, used in gastrointestinal cancer treatment. Alginate is a natural polysaccharide used in the pharmaceutical industry due to its physicochemical properties, biocompatibility and non-toxicity. Multivalent cations, exposure time and cross-linking solution concentration were optimized, being Sr2+, 2 h and 0.2 M the best immobilization conditions. Furthermore, compression strength, swelling ratio and fracture frequency were evaluated, improving the mechanical stability of the biocatalyst favoring a future scale-up. On the other hand, the reaction parameters for 5FUradRib biosynthesis were optimized in order to obtain an immobilized biocatalyst with enhanced activity. Thus, Lactobacillus animalis ATCC 35046 immobilized in Sr-alginate showed yields of 96% at short reaction times. The obtained biocatalyst was stable for more than 25 days in storage conditions (4 °C) and could be reused at least 10 times without loss of its activity. Additionally, Sr-alginate biocatalyst stability was evaluated in different organic solvents to obtain hydrophobic compounds such as 5-bromouracil-2′-deoxyriboside (5BrUradRib), an effective radiosensitizing agent used in anti-cancer therapy, being hexane the best co-solvent. Finally, a smooth, cheap and environmentally friendly method to obtain anti-cancer drugs was developed in this study.